Design And Development Of Saltwater Lamp (Aluminum-Copper Saltwater Lamp & Aluminum-Air Saltwater Lamp) - Muhammad Nur Najmi, Ibrahim (2023)
This study aimed to design, develop, and compare aluminum-air and aluminum-copper saltwater lamps to determine the best option for usage. The methodology involved designing the saltwater lamps, producing them, and conducting tests to gather data on voltage, current, and luminance readings. The results showed that both saltwater lamps were successfully produced and that the aluminum-air saltwater lamp produced higher luminance compared to the aluminum-copper saltwater lamp due to higher current and voltage readings. The conclusion is that the design and production of both saltwater lamps was successful, and the aluminum-air saltwater lamp is the better option for providing light. Recommendations for future improvements include using smaller cathodes and anodes, incorporating solar technology, using alternative catalysts to replace graphite, and using the saltwater lamp as a guide to create a power generator.